Methionine-loading rapidly impairs endothelial function, by mechanisms independent of endothelin-1: evidence for an association of fasting total homocysteine with plasma endothelin-1 levels. - Tousoulis, D; Antoniades, C; Marinou, K; Vasiliadou, C; Bouras, G; Stefanadi, E; Latsios, G; Siasos, G; Toutouzas, K; Stefanadis, C (2008)
OBJECTIVE: Homocysteinemia is associated with elevated oxidative stress and impaired endothelial function. In the present study we examined the impact of oxidative stress in the development of endothelial dysfunction in both chronic and acute (methionine-induced) homocysteinemia in humans. We also examined the role of endothelin-1 (ET-1) in the development of endothelial dysfunction in these two conditions. METHODS: In this double-blind placebo controlled study, 28 subjects of both genders (14 with homocysteinemia and 14 healthy controls) underwent methionine-loading (100mg/Kg body weight) in a standard juice, containing vitamins C (2g) plus E (800IU) (n = 14) or no vitamins (placebo group, n = 14). Forearm vasodilatory response to reactive hyperemia, plasma total homocysteine (tHcy), oxidized LDL (ox-LDL), ET-1 and soluble vascular cell adhesion molecule (sVCAM-1), were evaluated at baseline and 4 hours post methionine loading (4hPML). RESULTS: Chronic homocysteinemia was associated with increased oxLDL (p < 0.01), higher ET-1 (p < 0.05) and impaired endothelial function (p < 0.01). However, oxLDL (but not ET-1) was increased 4hPML in the placebo group, an effect prevented by antioxidant vitamins. The development of severe endothelial dysfunction 4hPML was not however prevented by antioxidants. In linear regression analysis, fasting tHcy was an independent predictor of baseline oxLDL (p = 0.0001), but not of ET-1 levels. On the contrary, oxLDL was the main predictor of ET-1 (p = 0.008), suggesting that tHcy may increase ET-1 by enhancing the production of oxLDL. CONCLUSIONS: Both chronic and acute methionine-induced homocysteinemia are associated with elevated oxidative stress status. Although ET-1 is increased in chronic homocysteinemia, it does not participate in the rapid development of endothelial dysfunction after methionine loading. These findings suggest that despite its potential role in chronic homocysteinemia, ET-1 has a limited contribution to the development of endothelial dysfunction in acute, methionine-induced homocysteinemia in humans.